Using Bootstrap Fourier Granger Causality Test in Quantiles to Re-examine Pollution Haven/Halo Hypotheses in China and G3 Countries - Tsangyao, Chang; Chen, Sheng-Tung; Wang, Mei-Chih (Panoeconomicus, 2024)
We re-examine the Pollution Haven and Pollution Halo hypotheses (PHEH and PHALH) using a quantile-based Bootstrap Fourier Granger causality test, a method adept at identifying non-linear structural breaks. Our study encompasses data from China and the G3 countries (Japan, the UK, and the USA) spanning the period from 1980 to 2020. Our empirical findings reveal that data from the USA corroborates the PHEH, suggesting a trend where increased foreign direct investment (FDI) aligns with higher environmental degradation. In contrast, data from China affirms the PHALH, indicating that FDI contributes to improved environmental standards. However, data from Japan and the UK do not conclusively support either hypothesis. These results have significant implications for governmental policy formulation in China and the G3 countries, particularly in shaping FDI policies that align with environmental sustainability goals. JEL: Q56, F18, C32, F21, Q54